Comprehensive computational investigations on various aerospace materials under complicated loading conditions through conventional and advanced analyses: a verified examination - Gnanasekaran, Raj Kumar; Shanmugam, Balasubramanian; Raja, Vijayanandh; Al-Bonsrulah, Hussein A. Z.; Rajendran, Parvathy; Radhakrishnan, Jeeva; Eldin, Sayed M.; Narayanan, Venkatesh (Frontiers in Materials, 2023)
Most failures develop as a result of a lack of resistivity information at the internal structure level during typical loading situations such as shock load, impact load, and so on. Impact loads have a significant impact on a component's structural performance. A careful, organised examination of impact load settings and their side effects can reveal how well something can withstand peak loads. Firstly, this paper investigated the impact analyses on various nine lightweight composite materials through conventional experimental setup and computational tool. And so, the best the three lightweight materials are shortlisted for further investigation under complicated explicit analysis. Secondly, the paper investigated the behaviour of composite materials subjected to rapid loading circumstances in several real-time applications. The applications chosen include bullet crash analysis, UAV propellers, and car bumpers. The three principal different composites, CFRP, GFRP, and KFRP, are selected and applied in crash analysis using ANSYS Workbench's Explicit technique based FEA. The comparison assessments are conducted using stumpy structural characteristics such as impact stress and equivalent strain. Two distinct grid convergence tests were performed to check that the computational processes and discretization were correct. The standard methodologies were used to all three selected real-time applications, resulting in error percentages that were within acceptable bounds, ensuring the generation of dependable structural outputs. The ideal composite material is a Kevlar fiber-based composite with minimal defect affectability for all types of crash applications. Furthermore, multidisciplinary optimizations are performed, and the KFRP is verified to give good crash load resistance with a reduced dense contribution.